Anti-tumour necrosis factor (TNF) α treatment of rheumatoid arthritis (infliximab) selectively down regulates the production of interleukin (IL) 18 but not of IL12 and IL13. Issue 8 (1st August 2002) - Pittoni, V; Bombardieri, M; Spinelli, F R; Scrivo, R; Alessandri, C; Conti, F; Spadaro, A; Valesini, G
Abstract : Objective: To measure interleukin (IL)18 serum concentrations in patients with rheumatoid arthritis (RA) undergoing infliximab treatment (tumour necrosis factor (TNF) α blockade) and to evaluate the concomitant modification of IL12 and IL13 serum concentrations, two cytokines belonging to the Th1 and Th2 profile respectively and biologically related to IL18. Methods: Ten patients with RA not responding to disease modifying antirheumatic drugs (DMARDs) received intravenous infliximab at a dose of 3 mg/kg at baseline and after two and six weeks. Serum samples were collected from all patients before each infusion and assayed for IL18, IL12, and IL13 by enzyme linked immunosorbent assay (ELISA); IL18 was also measured eight weeks after the last infusion. Results: Serum concentrations of IL18 in all patients were already markedly reduced from baseline after two weeks (p<0.005). Serum IL18 was also decreased in a stable manner after six (p<0.01) and 14 weeks (p<0.01) compared with baseline concentrations. No significant modifications were found in serum concentrations of IL12 and IL13 at any time point. Conclusion: There was a rapid and persistent decrease in serum concentrations of IL18 in all the patients studied. This result provides evidence of an in vivo regulation of IL18 by TNFα and suggests that anti-TNFα therapy is likely to interrupt the synergistic effect between these two cytokines.